Outcome comparison between muscle and fasciocutaneous flaps after secondary orthopedic procedures. (February 2023) - Guo, Meng; Thomas, Bejoy; Goyal, Samita; Rivedal, David; Mehdi, Maahum; Schmeling, Gregory J.; Neilson, John C.; Martin, Jill; Harkin, Elizabeth A.; Wooldridge, Adam; King, David M.; Hackbarth, Donald A.; et al.
Summary: Lower extremity wounds associated with fractures and bony defects often require secondary orthopedic procedures after flap coverage has been performed. In this study, we compare complications between muscle and fasciocutaneous flaps after secondary orthopedic procedures. A retrospective chart review study of all lower extremity soft tissue reconstructions by a single surgeon over seven years yielded a subgroup of patients who underwent secondary orthopedic procedures, including hardware removal, hardware revision, and bone grafting after flap reconstruction. Of 355 lower extremity, soft tissue reconstructions for orthopedic coverage performed in the time period studied, 102 patients underwent secondary orthopedic procedures after flap reconstruction. Of these, 54 received muscle flaps (52.94%), and 48 received fasciocutaneous flaps (47.06%). Using this subgroup of 102 patients, we compared muscle and fasciocutaneous flaps using three categories of wound complications following these secondary procedures: There were no superficial wounds requiring local wound care only in the muscle flap group (0%, n  = 0) versus 4.17% ( n  = 2; p  = 0.130) in the fasciocutaneous flap group. There were 2 lost flaps requiring surgical debridement and additional skin grafting in the muscle flaps group (3.70%) versus 2 (4.17%; p  = 0.904) in the fasciocutaneous flap group. In the third category, flap loss requiring additional soft tissue reconstruction was 18.52% ( n  = 10) in the muscle group versus 2.08% ( n  = 1; p  = 0.008) in the fasciocutaneous flap group. Our data support the existing literature indicating that fasciocutaneous flaps can tolerate secondary procedures better than muscle flaps and should initially be considered in patients with higher probability of needing additional orthopedic procedures after reconstruction.